2011
DOI: 10.4100/jhse.2011.62.21
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and physical fitness traits of four-time World Greco-Roman wrestling champion in relation to national norms: A case study

Abstract: Mirzaei B, Curby DG, Barbas I, Lotfi N. Anthropometric and physical fitness traits of four-time World GrecoRoman wrestling champion in relation to national norms: A case study. J. Hum. Sport Exerc. Vol. 6, No. 2, pp. 406-413, 2011. The purpose of the present investigation was to describe the anthropometric and physical fitness traits of a four-time World senior Greco-Roman wrestling champion (age: 24 years, height: 167 cm, weight: 61 kg) in relation to national norms. The anthropometric traits included body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
43
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 9 publications
6
43
1
4
Order By: Relevance
“…One of greatest features of wrestlers is the strength of upper and lower body (1RM) chest press and squat were 72.88 and 100.27 kg respectively. All the aforesaid amounts were less than Mirzaei et al's findings [23] and followed the national norm of Iran [3].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…One of greatest features of wrestlers is the strength of upper and lower body (1RM) chest press and squat were 72.88 and 100.27 kg respectively. All the aforesaid amounts were less than Mirzaei et al's findings [23] and followed the national norm of Iran [3].…”
Section: Discussionmentioning
confidence: 66%
“…Mirzaei et al stated that the flexibility record among various weight range was very close to each other [3]. However, in a case study Mirzaei et al reported the sit and reach test as 45cm [23]. In contrast, some experimental researches concluded that when the wrestlers' muscle strength increases, their flexibility does not decrease [22].…”
Section: Discussionmentioning
confidence: 87%
“…They reported that the arm-span of the subject was 7 cm more than his height. Because having long arms is a mechanical advantage in Greco-Roman wrestling, this trait may one of the reasons for successful performance of the wrestler in techniques such as the reverse lift and gut-wrench (9). Mirzaei and Ghafouri (2007) studied the physiological profile of Iranian senior Greco-Roman wrestlers.…”
Section: Introductionmentioning
confidence: 98%
“…Frequent changes in wrestling rules during last ten years, especially rules related to duration of competition has exposed various physiological requirements of this Olympic sport with a lot of challenges including interference of aerobic and anaerobic energy systems, recovery between two competitions and measuring and evaluating physical fitness factors [13]. The factor that makes this matter more complicated is considering wrestling as a sport which need weight classification.…”
mentioning
confidence: 99%